PEMBERIAN PENDIDIKAN KESEHATAN KEPADA MASYARAKAT DAN KELUARGA DALAM MERAWAT ANGGOTA KELUARGA DENGAN GANGGUAN JIWA - Anggraini, Millia; Siska Yunere, Faleri; Yuliano, Aldo (COVIT (Community Service of Tambusai), 2022)
Mental health is a state of mental well-being that allows a harmonious and productive life, as an integral part of a person's quality of life by paying attention to aspects of human life. The prevalence of mental disorders worldwide according to WHO (World Health Organization) data in 2019, there are 264 million people experiencing depression, 45 million people suffering from bipolar disorder, 50 million people experiencing dementia, and 20 million people experiencing schizophrenia. This condition needs serious attention from all levels of cross-sectoral government both at the Central and Regional levels, as well as attention from the entire community, especially families. The lack of understanding of the community and families about how to treat patients with mental disorders and the stigma of society on mental patients will have a non-optimal impact on the recovery of family members who suffer from mental disorders. Where the field survey data found a statement that 85% of the people of Puhun Pintu Kabun Bukittinggi City lacked knowledge about people with mental disorders, community stigma in patients with mental disorders and how to treat patients with mental disorders at home. Health education and support from the community and family are very much needed by patients with mental disorders. The results of this community service show that there is an increase in community and family knowledge about mental disorders after being given education about knowledge of mental disorders in the community Keywords: Health Education, Mental Disorder